Alimentación, anemia, y riesgo en el desarrollo psicomotriz en niños de primera infancia de la I.E.I N° 172 Ángel de la Guarda, Iquitos 2022 - Guzmán Nuñez, Brenda (2023)
The research was conducted to establish the relationship between anemia, nutrition and the risk of psychomotor development in children aged 3 to 6 years of the I.E.I Nº 172 "Angel de la guard" of the city of Iquitos. The research had a quantitative, non-experimental correlational scope, with cross-sectional data collection, a hemoglobin data sheet was used as data collection instruments, as well as the feeding questionnaire, and the National Test for Screening of Inapparent Disorders of Psychomotor Development (PRUNAPE). The results show that 98.2% of the sample under study had an unhealthy diet, 21.1% had mild anemia, 11.0% had moderate anemia, and 41.3% reported a risk in psychomotor development. From the analysis of the relationship between variables with a significance value of 0.00 and 0.023, a relationship was established between diet, anemia, and the risk of psychomotor development. The study concludes that there is a relationship between nutrition, anemia and the risk of psychomotor development in early childhood children of the I.E.I "Angel de la guarda" of the city of Iquitos.